2019
DOI: 10.1002/app.48381
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐phasic water diffusion in sheet molding compound composite

Abstract: Sheet molding compound (SMC) composite has been studied under humid-aging conditions. Diffusion of water within the material, as measured by gravimetry, was found to be in good agreement with the "Langmuir-type" diffusion model developed by Carter and Kibler. In their theory, Carter and Kibler consider the existence of two types of water molecules in the material, «mobile» and «bound». In this study, these two types have been considered separately. Furthermore, Infrared spectroscopy (FTIR) analysis has been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…5 where the normalized water uptake data (as mass uptake/mass at saturation) are plotted versus the normalized time given by t 0.5 /e (where e is the sample thickness). Similar trends were obtained for samples aged at 25, 50 and 70 • C and can be found here [22]. It was found that the «mobile» water corresponding to the diffusion in the micro-porosities.…”
Section: Gravimetric Testssupporting
confidence: 89%
See 4 more Smart Citations
“…5 where the normalized water uptake data (as mass uptake/mass at saturation) are plotted versus the normalized time given by t 0.5 /e (where e is the sample thickness). Similar trends were obtained for samples aged at 25, 50 and 70 • C and can be found here [22]. It was found that the «mobile» water corresponding to the diffusion in the micro-porosities.…”
Section: Gravimetric Testssupporting
confidence: 89%
“…9, cross sections of the 90 • C aged composite after different water uptake are shown. Overall, the damage development in the aged SMC composite proceeded faster which is in line with the evolution in water uptake properties as discussed in the previous work [22].…”
Section: Damage Analysis Based On X-ray Micro-computed Tomographysupporting
confidence: 88%
See 3 more Smart Citations